The Impact of Entrepreneurial Networks, Orientation, and Competence on Online Trading SMEs Performance in Makassar City - Syulhasbiullah, Muh; Dwi Radianto, Wirawan Endro; Tambunan, Damelina Basauli (Universitas Dharma Wacana, 2025)
Research Aims: This study aims to examine the effect of entrepreneurial networks, entrepreneurial orientation, and entrepreneurial competence on the performance of online trading SMEs in Makassar City. It seeks to understand how these entrepreneurial factors contribute to SMEs’ success in the digital business environment.Design/Methodology/Approach: A quantitative approach was adopted using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through online questionnaires distributed to 150 SME owners operating in online trading in Makassar. The measurement model and structural model were assessed for validity, reliability, and hypothesis testing.Research Findings: The study found that all three variables — entrepreneurial networks, entrepreneurial orientation, and entrepreneurial competence — have a significant and positive influence on SME performance. Entrepreneurial orientation was the most dominant factor, followed by entrepreneurial competence and entrepreneurial networks. The model explained 83.4% of the variance in SME performance with high predictive relevance (Q² = 0.732).Theoretical Contribution/Originality: This research enriches the literature on entrepreneurial dynamics by empirically validating the interplay between entrepreneurial orientation, networks, and competence in the context of digital SMEs in emerging economies. It confirms the Resource-Based View (RBV) theory by showing how internal capabilities and external linkages enhance performance.Practitioners/Policy Implications: The findings provide practical guidance for SME owners to focus on building robust networks, enhancing managerial competencies, and fostering a proactive and innovative business mindset. For policymakers, the study highlights the need for support programs focusing on digital literacy, entrepreneurial training, and access to networking platforms.Research Limitations/Implications: This study is limited to online trading SMEs in Makassar City, which may affect the generalizability of findings to other regions or industries. Future research could explore longitudinal designs, incorporate moderating variables such as digital transformation or government support, and compare SMEs across multiple regions or sectors.